2016
DOI: 10.15268/ksim.2016.4.4.067
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Frontal Knee Alignment Measured by the HKA-Angle with the Relative Activation of the Quadriceps Muscles

Abstract: Purpose: The purpose of this study was to compare Hip-Knee-Ankle(HKA) angle and muscle activation ratio between vastus medialis(VM), rectus femoris(RF), and vastus lateralis (VL), and by this, to examine their relationship. It is aimed to explore how the activation ratio among the muscles involved in patellofemoral kinetics would vary in relation with the frontal alignment of the lower extremity.Subjects and Methods: 26 healthy subjects were recruited for the study. The HKA angles were measured with radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Controversial results and studies on whether larger quadriceps angle is more generative of PFP exist probably and partly for this reason 15 , 16 , 17 ) . Kim et al 18 ) reported in their study where they investigated the correlation between the hip-knee-ankle (HKA) angle and activation the muscles composing quadriceps that, the greater the HKA angle, the more medial muscle’s activation ratio increased in ambulation, which is similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Controversial results and studies on whether larger quadriceps angle is more generative of PFP exist probably and partly for this reason 15 , 16 , 17 ) . Kim et al 18 ) reported in their study where they investigated the correlation between the hip-knee-ankle (HKA) angle and activation the muscles composing quadriceps that, the greater the HKA angle, the more medial muscle’s activation ratio increased in ambulation, which is similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 88%
“…When exercising on a NMT or MT, different gait patterns occur even at the same given speed, creating different tasks in movement (S. M. C. Lee et al, 2008), while changes of speed and gait have been shown to effect muscle activation (Cappellini, Ivanenko, Poppele, & Lacquaniti, 2006). Recent studies have found correlations between a greater hip-knee-ankle (HKA) angle and an increase in medial muscle activation (Kim, Bae, Lee, & Lee, 2016;N. Lee, 2018), however in our study there was a significant difference only in the VL during the walking condition.…”
Section: Discussionmentioning
confidence: 99%